Peran Pengajian Ahad Pagi Cabang Muhammadiyah Dalam Menanamkan Nilai-Nilai Agama Islam Masyarakat Desa Tulung Kecamatan Tulung Kabupaten Klaten Tahun 2016-2017 - Ariyanti, Putri Suci, Drs.Saifuddin Zuhri, M.Ag (2017)
Muhammadiyah Branch Sunday Morning Preaching is one of the preaches organized by the Branch Chairman of Muhammadiyah referring to guidelines of Muhammadiyah branch revitalization. The objective of this study is a mean for Muhammadiyah to propagate the teachings of Islam in accordance with the guidance of the Qur'an and Sunnah to the whole society. Lack of knowledge of religion will affect the consciousness of citizens in performing acts of worship and religion. Some residents in the village Tulung are still lack in understanding of Islam perfectly, as citizens they still follow kenduren, salvation andyasinan and a lack of understanding of Islam. Therein lies the contributing role of Muhammadiyah Branch Sunday Morning Preachingto instill the values of Islam to the community in the Tulung village. The purpose of this study is to describe the implementation of Muhammadiyah Branch Sunday Morning Preaching and its roles in instilling the values of Islam to the community in theTulung village Tulung District of Klaten Regency Year 2016-2017. This research is a field research, whereas the type of approach used in this study is qualitative descriptive. Data collection methods used are interview, documentation, observation. While the method of data analysis used is descriptive qualitative inductive analysis. Based on data from the results of this study, it is concluded that Muhammadiyah Branch Sunday Morning Preachinghas been running well, namely by promoting methods used Bi al-Ḥikmah, Mau'iẒatul Ḥasanah, Mujādalah Billatī Hiya Aḥsanand the contents are suitable witheveryday community life so that the Islamic values in material creed, morals, worship and muamalahcan be realized well.Muhammadiyah Branch Sunday Morning Preaching in instilling Islamic values in the community of Tulung Village,Tulung District of Klaten Regency Year 2016-2017 are first, strengthen the preaching function as a place of Islamic teaching and guidance, ie with the activities of religious lectures. Second, make preaching as a skilldevelopment center. The community can hone their skills to read the Qur'an properly. Third, enhance the role of community empowerment through the development of economic and social potential, touched to get used to pay the donation, charity and fundraising humanity. Fourth, make the preaching as a medium of silaturrahmi and spiritual recreation. In addition to their science, the community can establish a relationship.